COMPARISON BETWEEN TWO FEEDING RATES AND THREE FEEDING FREQUENCIES FOR HYBRID SURUBIMS REARED IN CAGES - Bogiani, Juliana Sversut de Alexandre (2018)
This study evaluated the effects of feeding frequency and feeding rate on productive performance of hybrid surubims reared in cages with automatic feeding. Three feeding frequencies (6, 12 and 24 meals day-1), and two feeding rates (4% and 8% of body weight per day, BW day-1) were evaluated. Hybrid surubims (Pseudoplatystoma corruscans × Pseudoplatystoma fasciatum) with average weights of 24.20 ± 0.80 g were distributed in 18 cages of 1.0 m³ at a density of 60 fish m-3. Fish were fed commercial ration containing 40% crude protein, and feeding took place at night using automatic feeders. The study lasted 47 days. With a feeding rate of 4% BW day-1, the final weight (FW) of the surubims was higher when feed was supplied as 24 meals day-1 (66.92 g). However, using 8% BW day-1, the FW was greater with a feeding frequency of 12 meals day-1 (106.90 g). Regardless of feed frequency, the values of daily weight gain and standard length of surubims were higher with the feeding rate of 8% BW day-1. Therefore, the feeding rate of 8% BW day-1, provided in 12 meals day-1, provided better productive performance for hybrid surubims (Pseudoplatystoma corruscans × Pseudoplatystoma fasciatum) reared in cages.